Strategi Guru BK dalam Meningkatkan Prestasi Belajar Siswa Kelas IX di Madrasah Aliyah Negeri 1 Kota Binjai - Nun Zairina (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Abstract: The purpose of this study is to describe the strategy of BK teachers in improving student learning achievement in class IX MAN 1 Binjai City. The method used in this research is qualitative. The subjects of this study were BK teachers who had performed services that discussed improving student learning achievement. The instrument used was interviews that were collected and collected data related to research. Based on the results of research and data analysis, it can be concluded that the learning achievement of IX grade 1 MAN Binjai City is already quite good, there are only a few students who still have low learning achievement. The cause is the problem of students 'self-awareness for learning and students' inability to use several subjects. Guidance and Counseling Teacher strategies in improving student achievement in class IX MAN 1 Binjai City is a place to find students and fun that makes schools easier for BK teachers to find out which helps students. Next, a discussion and analysis of needs / students is carried out, then a program is compiled in the form of an RPL (Service Implementation Plan), then service implementation. Finally given an assessment or evaluation that is useful to know where an activity has been obtained and how the benefits have been done before. The inhibiting factors in the implementation of the guidance and counseling strategy in class IX MAN 1 Binjai City are lack of service delivery time, parents who are less supportive of service activities, and students who have no self-awareness to learn and no one wants to be changed.Keywords: BK Teacher Strategy In Improving Student Learning Achievement